Level of physical activity, eating habits, and their relationship with academic performance in adolescent students at COMEDUC foundation, Chile. - Ibarra Mora, Jessica
This study was aimed to determine the impact of the level of physical activity and eating habits in the academic performance of an adolescent school population in Chile. The study has a descriptive cross-cutting design. The sample was formed by 2116 students (60.8% women and 39.2% men), later it was stratified according to level of physical activity and eating habit. Habits were determined by means of a 24-hour reminder, the level of physical activity by means of the International Physical Activity Questionnaire, and the general school averages, mathematics and language, as well as standardized tests were considered. For the analysis of data, descriptive and inferential statistics were used. The results indicated that having a high level of physical activity and having the main meals per day is associated with a better school performance, highlighting the importance of promoting these habits among the school community.